THE EFFECTS OF A PHYSIOTHERAPEUTIC COMPLEX IN PATIENT WITH POST-TRAUMATIC STIFF ELBOW - Petar Petkov; Detelina Nedyalkova-Petkova; Evgeniya Vladeva; Liliya Panayotova-Ovcharova; Stoyan Ivanov (Journal of IMAB)
Elbow stiffness is a relatively common condition and represents a significant disability. A proper clinical history is essential for therapeutic surgical or non-surgical planning. Purpose: The study aims to investigate the possibility of treating and preventing elbow stiffness. Material and Methods: A 63-year-old woman was diagnosed with a fracture of the distal humerus and a fracture of the olecranon process. The fractures were treated in the prone position and with a dorsal approach to the elbow. The distal humerus was fixed with medial and dorsolateral locking plates, while the olecranon process was fixed with Webber osteosynthesis. After the operation, the woman required postoperative soft immobilisation for about 30 days. A seven-day treatment was conducted using a combination of Multiwave Locked System (MLS) laser therapy and kinesiotherapy techniques. Results: On day 1 /T1, after physical examination, the patient was diagnosed with significantly limited range of motion, pain at the end of motion, and swelling of the elbow. On day 7 /T2/ of the seven-day rehabilitation treatment cycle, we observed significant improvement in elbow contracture, range of flexion, reduced swelling, VAS scores, and Mayo Elbow Performance Index scores. Conclusions: The reported improvement in all the monitored indicators gives us reason to conduct a study on the application of a therapeutic protocol in patients with orthopedic implants of the elbow joint. The challenge in the treatment of postoperative contracture with limitation of movement in the elbow joint requires the inclusion of modern physiotherapeutic methods in its complex treatment.